Macro-dissemination of Maker Cultures: 21st century competencies through an Ideaton - Sanabria, Jorge; Davidson, Ann-Louise; Romero, Margarida; Quintana, Teresa (Revista de Educación a Distancia (RED), 2020)
With the aim of fostering innovation culture and entrepreneurship through directed ideation, a co-technocreative competition was held for 1000 high school students during the 2018 Innovation Festival Epicenter in Jalisco, Mexico. The competition objectives were aligned with the Sustainable Development Goals (SDG) of the UN, where the methodology was based on evoking practical and innovative solutions to the local problems of the eight strategic sectors of the state. The prototyping activity, guided by the Trayekta canvas, was characterized by the inclusion of programmable microcontrollers, sensors and motors, which allow the development of 21st century competencies, such as creativity, collaboration, critical thinking, computational thinking and problem resolution. The follow-up to participants was established for a year using a digital platform. The logistic scheme made in collaboration with the Ministry of Innovation, Science and Technology (SICyT) and the research design proposed between three universities in Mexico, Canada and France, are presented in this paper.